52.4k views
25 votes
For funcitons f(x)=2x+3 and g(x)=-3x-2, please find (f∘g)(-1)

User Josiah
by
5.2k points

1 Answer

6 votes

Answer:


\displaystyle (f\circ g)(-1) = 5

Explanation:

We are given the two functions:

\displaystyle f(x) = 2x + 3\text{ and } g(x) = -3x - 2

And we want to find:

\displaystyle (f\circ g)(-1)

Recall that this is equivalent to:

\displaystyle (f\circ g)(-1) = f(g(-1))

Hence, find g(-1):

\displaystyle \begin{aligned} g(x) & = -3x - 2\\ \\ g(-1) & = -3(-1) - 2\\ \\ & = (3) - 2 \\ \\ & = 1 \end{aligned}

Substitute:

\displaystyle f(g(-1)) = f(1)

Find f(1):


\displaystyle \begin{aligned} f(x) & = 2x+ 3 \\ \\ f(1) & = 2(1) + 3 \\ \\ & = 5\end{aligned}

In conclusion:

\displaystyle (f\circ g)(-1) = 5

User Loshkin
by
5.0k points